Asetilasi sulfadiasina pada asetilator lambat dan cepat=Acetylation of Sulfadiazine on Slow and Fast Acetylator - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT The pharmacokinetics of sulfadiazine have been studied in 14 healthy males of slow and rapid acetylators to investigate the possibility of wether or not the drug is polymerphically acetylated. The ages varied between 19.28 years and body weight range 50,0 to 70,0 kg. The determination of acetylator phenotype was carried out after the oral administration of 500 mg sulfadimidine, based on the ratio of acetylateci sulfadimidine in relation to the parent compound in 5-6 hour urine specimen. Various pharmacokinelic parameters of sulfadiazine were estimated after the ingestion of 500 mg of the drug given as single dose. Blood and urine samples were serially collected and free and total sul fadiazine concentration were assayed spectrophotometrically by Bratton - Marshall method. Parameters of the absorption kinetics and bio avaliability were not significantly different between both phenotypes. Neither was the values of volume distribution. Parameters of elimination kinetics, however, were significantly different in rapid and slow acetylators, especially those of metabolic elimination, indicating the more rapid ecetylation in the former. The higher rates of acelylation in the rapid ecetylator group suggest that sulfadiazine is most likely undergo olymorphic acetylation